2021
DOI: 10.1016/j.jtocrr.2021.100232
|View full text |Cite
|
Sign up to set email alerts
|

CADM1 and SPC25 Gene Mutations in Lung Cancer Patients With Idiopathic Pulmonary Fibrosis

Abstract: Introduction To investigate the genomic profiles of patients with lung cancer with idiopathic pulmonary fibrosis (IPF-LC), mechanism of carcinogenesis, and potential therapeutic targets. Methods We analyzed 29 matched, surgically resected, cancerous and noncancerous lung tissues (19 IPF-LC and 10 non–IPF-LC) by whole-exome sequencing and bioinformatics analysis and established a medical-engineering collaboration with the Department of Engineering of the Tokyo University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In OSCC, the prognostic value of TGF-β1 has still remained elusive. Nevertheless, there is a correlation between TGF-β1 signaling pathway and SPC25 expression levels 24) . Our data showed that silencing of SPC25 suppressed the TGF-β1/Smad signaling pathway, as evidenced by downregulated expression levels of TGF-β1, p-smad2, and p-smad3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In OSCC, the prognostic value of TGF-β1 has still remained elusive. Nevertheless, there is a correlation between TGF-β1 signaling pathway and SPC25 expression levels 24) . Our data showed that silencing of SPC25 suppressed the TGF-β1/Smad signaling pathway, as evidenced by downregulated expression levels of TGF-β1, p-smad2, and p-smad3.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of SPC25 expression levels was reported in prostate, lung, and breast cancer cells, and it significantly promoted the proliferation of these tumor cells [16][17][18][19]22) . SPC25 was engaged in the regulation of cell stemness 18) , proliferation 23) , and EMT 24) . A correlation was previously found between TGF-β1 signaling pathway and SPC25 expression levels 24) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation